Kejadian Depresi Postpartum Pada Ibu Yang Menikah Dini (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Postpartum depression is a psychiatric disorder that came a few days or thefirst week after birth. Postpartum depression though indirectly cause mortality but can causepain or morbidias to mother and child. Psychic disorders called postpartum depression canbe affected by characteristics of the mother's age. The factor of postpartum depression is inthe teenage years or